The Mediating Effect of Wisdom in the Relationship between Self-leadership and Quality of Service of Caregivers caring for Patients with Impaired Mobility and Elderly with Dementia - Hee Kyung Kim (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background/Objectives: The purpose of this study is to analyze the mediating effect of wisdom in therelationship between self-leadership and quality of service in caregivers who provide nursing services topatients and elderly.Methods/Statistical analysis: The subjects of this study were 96 caregivers from January to February2021. Data analysis is performed using SPSS Win 25.0 program, and were analyzed by correlation betweenvariables by Pearson correlational coefficients, and factors affecting service quality and mediating effects bymultiple linear regression and Sobel test.Findings: As a result of regression analysis to test the mediating effect of wisdom, in step 1, self-leadershiphad a significant effect on wisdom (?=.73, p<.001), in step 2, self-leadership affected the quality of service(?=.59, p<.001), in step 3, self-leadership had a positive effect on the quality of service (?=.26, p=.022), andwisdom also had a positive effect on the quality of service (?=.46, p<.001) and showed 44.9% explanatorypower. It was found that wisdom has a partial mediating effect.Improvements/ Applications: Education and training are needed to increase self-leadership and wisdomin caregivers in charge of visiting care. In particular, caregivers need to make efforts to acquire wisdom intheir daily lives.